FOLCKLORE AS PHYSICAL EDUCATION CLASS CONTENT IN MACAPÁ/AP (Fiep Bulletin - online, 2011)
The present study aims to investigate IF folklore/popular culture is used as Physical Education class content in the Educational System of Macapá city, Amapá. The research is characterized as descriptive investigation, having a semi-structured five question questionnaire as instrument. The volunteer intentional non-probabilistic sample was composed by 71 teachers, members of Public Schools of Macapá city. Results have been analyzed thematically and showed that folklore is not used as content or strategy by most of teachers. The main reasons alleged were lack of confidence to approach the theme due to lack of resources which may guarantee effective intervention, the superficial way that folklore as content is approached during graduation course and lack of continuing studies provided by public leadership. Teachers who used popular manifestations in their classes say that the most frequent ones are dancing and traditional games. This scenery shows the need for a change regarding knowledge related to popular culture in the teachers´ graduation as well as formulating public policies of continuing formation for teachers.
Keywords: Folklore; Popular culture; Physical Education